Measurement report: Assessment of Asian emissions of ethane and propane with a chemistry transport model based on observations from the island of Hateruma - A. R. Adedeji; S. J. Andrews; M. J. Rowlinson; M. J. Rowlinson; M. J. Evans; M. J. Evans; A. C. Lewis; A. C. Lewis; S. Hashimoto; H. Mukai; H. Tanimoto; Y. Tohjima; et al. (Atmospheric Chemistry and Physics, 2023)
The island of Hateruma is the southernmost inhabited island of Japan. Here we interpret observations of ethane (C2H6) and propane (C3H8) together with carbon monoxide (CO), nitrogen oxides (NOx and NOy) and ozone (O3) carried out in the island in 2018 with the GEOS-Chem atmospheric chemistry transport model. We simulated the mixing ratios of these species within a nested grid centred over the site, with a model resolution of 0.5∘ × 0.625∘. We use the Community Emissions Data System (CEDS) dataset for anthropogenic emissions and add a geological source of C2H6 and C3H8. The model captured the seasonality of primary pollutants (CO, C2H6, C3H8) at the site – high mixing ratios in the winter months when oxidation rates are low and flow is from the north and low mixing ratios in the summer months when oxidation rates are higher and flow is from the south. It also simulates many of the synoptic-scale events with Pearson's correlation coefficients (r) of 0.74, 0.88 and 0.89 for CO, C2H6 and C3H8, respectively. Mixing ratios of CO are simulated well by the model (slope of the linear fit between model results and measurements is 0.91), but simulated mixing ratios of C2H6 and C3H8 are significantly lower than the observations (slopes of the linear fit between model results and measurements are 0.57 and 0.41, respectively), most noticeably in the winter months. Simulated NOx mixing ratios were underestimated, but NOy appears to be overestimated. The mixing ratio of O3 is moderately well simulated (slope of the linear fit between model results and observations is 0.76, with an r of 0.87), but there is a tendency to underestimate mixing ratios in the winter months. By switching off the model's biomass burning emissions we show that during winter, biomass burning has limited influence on the mixing ratios of compounds but can represent a more sizeable fraction in the summer. We also show that increasing the anthropogenic emissions of C2H6 and C3H8 within the domain by factors of 2.22 and 3.17 increases the model's ability to simulate these species in the winter months, consistent with previous studies.